A Learning Community of Colleagues Enhancing Practice. (2nd April 2016) - Visone, Jeremy D.
Abstract: This article shares a promising practice: collegial visits. During collegial visits, educators watch a colleague teach a lesson about a predetermined focus as a form of professional development. Educators, including the host teacher, debrief after the lesson. These visits are part of a cycle of learning that moves from theory to practice, and the model is grounded in the research about professional learning communities. Collegial visits help foster a culture of sharing and collective ownership, while empowering teacher leadership .